P532 Safety and efficacy of endoscopic dilation of small bowel Crohn's disease strictures by balloon-assisted enteroscopy: pooled analysis of individual data from 210 patients. (25th January 2019) - Bettenworth, D; Bokemeyer, A; Kou, L; Lopez, R; Halloran, B P; Reeson, M; Hosomi, S; Kishi, M; Hirai, F; Ohmiya, N; Rieder, F
Abstract: Background: Strictures are a common complication of Crohn's disease (CD). While colonoscopy has been proven suitable and effective for dilation therapy of CD-associated strictures of the ileocaecum, the published evidence on safety and efficacy of balloon-assisted enteroscopy (BAE) for balloon dilation therapy of CD strictures of the small intestine is scarce. We therefore performed a pooled safety and efficacy based on individual patient data. Methods: A systematic literature review was performed to assess all relevant citations found in Embase, Medline and the Cochrane library regarding BAE used for EBD of small intestinal CD strictures. In addition, conference proceedings including DDW, ECCO, UEGW, A-IBD, AGA and German Gastroenterology Congress were screened for additional data. Study authors were contacted to provide individual patient data. Descriptive statistics were used to summarise patients' characteristics. Univariate cox proportional hazards regression model was applied to find out possible risk factors for need for re-dilation and surgery. Backward model selection procedure was used and multi-variate cox model were built. Results: 19 publications with a total of 468 CD patients and 1194 performed dilation procedures were included. 25.1% of strictures were anastomotic strictures (74.9% de novo, , respectively). Technical success rate was 88.1%, resulting in clinical efficacy in 78% of patients. Major complications defined as perforation, bleeding or dilation-related surgery occurred in 3.7% of all procedures. During a mean follow-up period of 16 months, 45.7 of patients reported symptomatic recurrence, while 38.1% of patients needed to undergo re-dilation and 27.5% required surgical intervention. Multi-variate analysis of 210 individual patients identified a 56% higher hazard of re-dilation in CD patients with symptomatic recurrence compared with asymptomatic patients and a 60% higher hazard in patients with prestenotic dilation compared with patients with no prestenotic dilation. Additionally, increased CRP values at dilation (elevation of CRP per 0.1 increased the hazard for surgery by 9.3%) and inflamed mucosa at dilation (4 times increased hazard when compared with non-inflamed mucosa) were identified as risk factors for the need for surgery. Conclusions: Balloon-assisted enteroscopy for dilatation therapy of CD-associated strictures of the small intestine possesses a high rate of short-term technical and clinical success with acceptable complication rates. Main predictors for intermediate therapeutic failure are prestenostic dilation, increased CRP values and mucosal inflammation at the time of dilation. Endoscopic dilation by BAE is a valuable alternative to surgery in selected patients with small bowel CD associated strictures.